STUDI STUDI KRITIS PEMIKIRAN RIJAL AL DA’WAH SYAIKH MUHAMMAD AL GHAZALI : (Telaah Kitab Al Sunnah al Nabawiyyah baina Ahl al Fiqh wa Ahl al Hadits) - Imam Taufik Alkhotob (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2024)
Abstract The presence of Rijal al-Da’wah has a significant impact on society, with their thoughts and movements drawing attention. One such figure is the da’i Muhammad Al Ghazali. This study aims to analyze Muhammad Al Ghazali's views in his book Al Sunnah al Nabawiyyah baina Ahl al Fiqh wa Ahl al Hadits, particularly concerning four crucial themes: the possession by jinn, the rejection of the hadith narration from Nafi’ maula Ibn Umar, the validity of hadith ahad, and the status of hadith Nisfu Sya’ban. The research employs a qualitative method with a library research approach, including content analysis of relevant primary and secondary texts. The findings indicate that, although Al Ghazali is a prominent figure in da’wah, some of his views contradict the consensus of Ahlusunnah wal Jamaah scholars. The impact of this research is to provide a deeper understanding of the strengths and weaknesses of Al Ghazali's perspectives, while emphasizing the importance of knowledge-based critique in religious discussions, enabling society to discern accurate and objective information.